Stress Experienced and Meaning-Making of Couples with Children with Autism Spectrum Disorder: A Phenomenological Study. Issue 1 (16th October 2020) - Romney, Justin; Austin, Kelsey; Fife, Stephen T.; Sanders, Daniel; Snyder, Hailey
Abstract: Couples who have a child diagnosed with autism spectrum disorder experience more stress than parents of neurotypical children. The purpose of this study is to understand the stress experiences of couples with a child diagnosed with autism and the meaning-making in their relationship. We conducted interviews with 18 couples ( N = 36) utilizing a phenomenological methodology to collect and analyze the data. Themes for stress experienced by couples included the child's behaviors, taking out stress on one another, lack of resources, and accommodating the child. Themes for couples finding meaning in stress included togetherness, religious views, adaptability, prioritizing marriage, and communication.